Improving the quality of psychiatric residency training in Isfahan University of Medical Sciences by learning teams and changing curriculum implementation: An action research study - Afsaneh Karbasi Amel; Sepideh Jamshidian; Fariba Haghani (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: The deficiencies in the training of psychiatric residents in Isfahan, including the segregation of residency programs by year, the confinement of training to hospital departments, and the residents' limited exposure to the perspectives of other faculty members, had not been given significant attention. However, the inevitable alterations in the Department of Psychiatry and the impact of the coronavirus disease 2019 pandemic have brought these issues to the forefront, highlighting the need for program modifications. The objective of this study is to enhance the quality of psychiatric residency training by changing the implementation of the curriculum. METHODS AND MATERIALS: This proactive action research was conducted in six steps. In the first step, the expectations of a new action were identified. In the second step, the new action - creating learning teams - was designed and implemented; thus, eight learning teams comprising experienced professors, novice professors, and residents from various academic levels were created, who collectively engaged in patient visits, psychotherapy, counseling, and educational sessions. Additionally, the portfolio was used in the training and evaluation of the residents. Steps 3 to 6 involved evaluation using a researcher-made questionnaire, analysis and interpretation of results, and reflection and making decisions for future actions. RESULTS: Step 1 resulted in preparing a list of department expectations from new action. The second step yielded the design of a new action. The survey results showed that more than 60% of respondents agreed that the program had a positive impact on 12 out of 15 items in the questionnaire, particularly in enhancing teamwork skills, facilitating discussions about patients, and fostering residents' accountability. However, in items related to portfolio, this percentage ranged from 40% to 53%. CONCLUSION: The implementation of learning teams as the main action in the current study has yielded positive outcomes; however, the portfolio intervention requires some adjustments. Hence, it is advisable to employ learning teams in comparable circumstances. The research team anticipates that these outcomes will enhance the quality of psychiatric residency training, positioning the country among the leading and influential nations in the region.